Earnings Prospects for People with Migration Background in Germany - Stephan L. Thomsen; Johannes Gernandt; Alisher Aldashev (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Less than half of the people with migration background living in Germany possess foreign citizenship. Hence, using citizenship to analyze economic issues of immigration may be problematic for two reasons. On the one hand, a quite substantial share of persons with migration background is neglected in the group of interest, and, on the other hand, the reference group (native Germans) may be contaminated by effects from naturalized immigrants. This paper utilizes a wider definition covering all persons with migration background to analyze the earnings prospects. To shed light on differences to the common use of citizenship, estimates are presented in comparison to foreigner and German citizens. The results show that persons with migration background have similar earnings prospects to foreigners. Moreover, earnings prospects for native Germans do not differ much from those of German citizenship. Therefore, using citizenship to approximate natives and non- natives when analyzing earnings issues seems to be reasonable. A second question of the paper is whether degrees obtained in Germany lead to better earnings prospects compared to degrees obtained abroad for persons with migration background. Independently of gender and skill level, the estimates affirm higher earnings to educational attainment in Germany.
Older version: http://hdl.handle.net/10419/24595
Keywords: J61; I12; J15; 330; Migration background; earnings prospects; education; Germany; Migranten; Einkommen; Bildungsertrag; Ausländer; Deutsche; Vergleich; Deutschland